Factors Affecting Participation in Online Communities of Practice - Mahar, Gerald Joseph (University of Waterloo, 2009)
Communities of practice are groups of people who share a concern, a set of problems or a passion about a topic, and who deepen their knowledge and expertise in this area by interacting on an ongoing basis (Wenger et al, 2002). An understanding of why working, technical professionals participate in knowledge- based communities of practice can provide better opportunities to support individual and organizational knowledge management strategies. Online communities of practice were investigated at two global corporations: Xerox and IBM. At Xerox, Eureka is an internal network service designed to support knowledge sharing and problem solving by a community of practice for field service technicians. It allows the submission of problems from field service technicians and the retrieval of validated solutions for use and adaptation, by all members of the global Eureka community. At IBM Corporation, public network based communities of practice were investigated that focused on db2™ and Websphere™ software technology. Unlike the Xerox Eureka community of practice, knowledge contributions at IBM communities of practice are not validated prior to submission and access is open to public participation globally by IBM employees and by independent users of IBM software technology. The purpose of this case study research was to explore and to describe how and why participants became members of communities of practice – what influenced them to join and to participate. We collected survey data from participants in these communities, to examine the relationships among members’ expectations of purpose, their relationship to the community of practice, their attitudes toward information handling, the costs and benefits of membership, the size of the community of practice and the resulting participation behaviour in these knowledge-based communities of practice at Xerox Corporation and IBM Corporation. As one aspect of exploring user behaviour, we investigated the applicability of two theoretical frameworks for understanding user behaviour in these communities, based on propositions from normative and utility theory and from public goods critical mass theory. The research study provides a test for the explanatory power of public goods, utility and normative theories in a new area; namely, online knowledge-based communities of practice in workplace contexts. This analysis provided support for the applicability of utility theory and for some aspects of public goods-based theory/critical mass theory. The findings of the case study point out some differences in the two communities of practice. A majority of the IBM-based community members reported belonging to multiple communities (6-10) and using access to the community to form online social networks and to meet members outside the community at in-person meetings. They reported their participation as being self-directed and on an ad hoc basis. Most respondents were community members for less than 2 years. In contrast, a majority of Eureka members reported belonging only to the Eureka community and do not report forming online social networks in Eureka. Participation in Eureka is seamlessly integrated into prescribed, standard work practices of the company and supported by company management and with resources. Most respondents were community members for over 5 years. The analysis of members’ contributing behaviour in two online communities of practice reaffirms that the majority of members are passive participants with a core group of regular message contributors. Message composition is a careful and deliberate activity requiring communication discipline, time and effort. Members in both settings reported a strong desire to spend more time in their communities (and more time per visit). Communities of practice are dynamic complex entities that present not only a theoretical challenge but also a practical challenge. This study’s results point to the complexity of facilitating communities of practice: benefits dynamics and flow and permanence dynamics of membership can only be externally managed to a limited extent. The participants’ roles need to be conceptualized in ways that support different types of participation while at the same time highlighting the inherently cooperative nature of self-managed communities of practice.
Keywords: Dynamics of Participation; Online Communities of Practice; Management Sciences